Applying the Total Productive Maintenance Principle to Improve the Maintenance System in a Food Company - Branská, Lenka; Pecinová, Zuzana; Paták, Michal (STEF92 Technology Ltd., 2016)
At present, production companies are working out their material flow management system not only at the corporate level, but also towards their customers. A way to improve the service to the enterprise’s direct customers as well as end consumers is developing cooperation with partners in the supply chain. This may lead further to the application of modern technologies of material flow management, such as the Quick Response or CPFR (Collaborative Planning, Forecasting and Replenishment). A necessary condition for successful implementation of these methods is the reliability of production equipment. That can only be secured by a functional maintenance system, which must be also optimal with regard to the resources expended. A way to increase the functionality of corporate maintenance systems can be implementation of methods such as 5S, TPM (Total Productive Maintenance), RCM (Reliability Centred Maintenance) or at least their basic principles. The decision on the method of improving the corporate maintenance system and the way of its application is based on the analysis of the reasons for problems in the manufacturing facilities. The paper presents the results of a primary qualitative research conducted in a food industry company. The company operates in a harsh competitive environment, and therefore failures to supply goods to customers threaten not only the financial health of the company, but even its very existence. The article describes the maintenance system for strategic production equipment. It analyses the key impacts of its high failure rate. Subsequently, the paper discusses the possibilities for improving the system of maintenance of production equipment in order to increase its reliability. It analyses the main causes of accidents and disproportionately long downtimes. By identifying the key issue it proposes to implement the principles of the method of TPM.
APLIKACE PRINCIPU TOTAL PRODUCTIVE MAINTENANCE PRO ZLEPŠENÍ SYSTÉMU UDRŽBY V POTRAVINÁŘSKÉM PODNIKU
Keywords: production equipment; maintenance; total productive maintenance; food industry; výrobní zařízení; údržba výrobního zařízen; TPM